High prevalence of hypertension among smokers of conventional and e-cigarette: Using the nationally representative community dwelling survey - Kim, Soo Young; Jeong, Sung Hoon; Joo, Hye Jin; Park, Minah; Park, Eun-Cheol; Kim, Jung Hyun; Lee, Junbok; Shin, Jaeyong (Frontiers in Public Health, 2022)
This study aimed to clarify the association between hypertension and conventional cigarette and electronic cigarette (e-cigarette) use, together or individually. A total of 275,762 participants were included, of which 120,766 were men and 154,996 were women. The data were drawn from the Korea Community Health Survey conducted in 2019. A multiple logistic regression model was used to examine the association between hypertension and types of smoking. Hypertension was defined as systolic blood pressure higher than 140 mmHg or diastolic blood pressure higher than 90 mmHg. Based on the types of smoking, participants were grouped as dual smokers of conventional and e-cigarettes, e-cigarette only smokers, conventional cigarette only smokers, past-smokers, and non-smokers. Compared to non-smokers, dual smokers presented the highest odds ratio for hypertension in the male [odds ratio (OR): 1.24, confidence interval (CI): 1.10 to 1.39] and female groups (OR: 1.44 CI: 0.96 to 2.15). According to the Cochran-Mantel-Haenszel test, the two-sided p-value of < 0.001 indicated an overall statistically significant association between types of smoking and hypertension. Use of both cigarette types was statistically significant in the male group, but only the use of conventional cigarettes and past smoking were statistically significant in the female group. Among smokers of the two cigarette types, those who were dual smokers of e-cigarettes and conventional cigarettes were the most likely to have the highest prevalence of hypertension.